PENYELESAIAN PENYIDIKAN PERKARA TINDAK PIDANA PENCEMARAN NAMA BAIK MELALUI RESTORATIVE JUSTICE (Kajian Perpol No.8 Tahun 2021) - Indriani, Novita; Faozi, Safik (Legal Standing : Jurnal Ilmu Hukum, 2023)
This research discusses the mechanisms for resolving cases of criminal defamation and legal certainty through restorative justice based on the Regulation of the Indonesian National Police Number 8 of 2021. This research method was carried out by researchers using the sociological juridical research method. Based on research and discussion, criminal acts of defamation can be resolved through the restorative justice system. This settlement involved the victim, the perpetrator, and the victim's family. Restorative justice prioritizes a win-win solution, seeking the best agreement for victims and perpetrators. The process of resolving criminal acts of defamation through restorative justice involves a meeting between the victim and the perpetrator as a form of accountability for the perpetrator. The success of this settlement depends on the good intentions of the victim and perpetrator. Restorative justice involves the community, victims and perpetrators in solving criminal acts of defamation. It is important to find a win-win solution to create justice for all parties. This settlement also puts forward persuasive and educational efforts to prevent criminalization and create an ethical, healthy, clean and productive digital space in Indonesia.